KESEJAHTERAAN RUMAH TANGGA PENGOLAH IKAN TERI ASIN DI PULAU PASARAN KECAMATAN TELUK BETUNG BARAT KOTA BANDAR LAMPUNG - Kurniati Mahasari; Dyah Aring Hepiana Lestari; Yaktiworo Indriani (Lampung University, 2014)
The purposes of this research were to analyze the household welfare level and household welfare distribution of salted anchovy fish processors. This research was conducted by survey method in Pasaran Island Sub-District of Teluk Betung Barat of Bandar Lampung City. This location was selected on purpose for it is the center of salted anchovy fish producer in Bandar Lampung. All of the 38 active salted fish producers were recruited as respondents of this research. The data analysis used in this research was descriptive qualitative and quantitative analysis (statistics). The household wealth distribution was calculated by the Gini index. The results of this research showed that based on the indicator of BPS, the welfare of all households of salted anchovy fish producers were classified as the prosperous classes. Likewise, based on the criteria of Sajogyo, all of them were classified as rich households. of the household expenditure approach, it showed that their value of Gini ratio based on Oshima criteria was 0.0948 for food expenditure, 0.1586 for non-food expenditure, and 0.1108 for total household expenditure. While based on the World Bank criteria, 40 percent of food expenditure processing salted anchovy fish with the lowest expenditure amounted to 35.35 percent, non-food expenditures amounted to 31.73 percent, and household spending was 34.78 percent. This suggests that low levels of inequality. Key words: expenditure, household, salted anchovy fish, welfare